Artist Bảo extended interview transcript (English) - Rachel Tough (22468807) (2025)
Transcript of Artist Bảo's extended interview with Co-I Phạm Thanh Thôi (English). Topics include his artistic training, mentor, career trajectory, family life, Vietnam's advertising industry, his future plans and hopes for the profession.